PENGARUH KOMPETENSI, GAYA KEPEMIMPINAN, DAN LINGKUNGAN KERJA TERHADAP KINERJA PEGAWAI APARATUR SIPIL NEGARA MELALUI KEPUASAN KERJA SEBAGAI VARIABEL INTERVENING DI UPT PUSKESMAS BESUKI - Dwi Rizkianto; Randika Fandiyanto; Ediyanto Ediyanto (Jurnal Mahasiswa Entrepreneurship (JME), 2026)
Health is a key factor in improving people’s quality of life, and community health centers play a vital role in providing optimal health services. This study aims to analyze the influence of competence, leadership style, and work environment on the performance of civil servants through job satisfaction at the Besuki Community Health Center. The study employed a saturated sampling technique, with data analyzed using the Structural Equation Modeling–Partial Least Squares (PLS-SEM) method. The results of the hypothesis testing on direct effects using the Smart PLS 3.0 application indicate that (1) Competence has a positive but insignificant effect on job satisfaction. On the other hand, (2) Leadership style has a positive and significant effect on job satisfaction. (3) The work environment also has a positive, albeit modest, effect on job satisfaction. Additionally, (4) Competence has a positive but insignificant effect on performance; (5) Leadership style among supervisors at the Besuki Community Health Center actually has a positive but insignificant effect; (6) A conducive work environment and adequate facilities and infrastructure are in place, but although they have a positive effect, it is not significant regarding performance. Meanwhile, (7) job satisfaction has been shown to have a positive and significant impact on employee performance. (8) Competence has a positive influence on employee performance through job satisfaction, although the effect is not significant. (9) Leadership style has a positive and significant impact on employee performance through job satisfaction. On the other hand, (10) the work environment also has a positive impact, though not as substantial, on employee performance through job satisfaction.